2004
DOI: 10.1529/biophysj.104.044925
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Linker Domain and the 203–214 N-Terminal Residues in the Human Topoisomerase I DNA Complex Dynamics

Abstract: The influence of the N-terminal residues 203-214 and the linker domain on motions in the human topoisomerase I-DNA complex has been investigated by comparing the molecular dynamics simulations of the system with (topo70) or without (topo58/6.3) these regions. Topo58/6.3 is found to fluctuate more than topo70, indicating that the presence of the N-terminal residues and the linker domain dampen the core and C-terminal fluctuations. The simulations also show that residues 203-207 and the linker domain participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
4
24
0
Order By: Relevance
“…The identical religation rate of the wild-type and the mutated enzyme is actually an unexpected result since it has been suggested that Thr-718 plays a role in the right positioning of the 5′ end through a hydrogen bond between the aminoacidic hydroxyl group and the G+2 phosphate group of the scissile strand (8). The MD trajectory confirms the importance of this hydrogen bond since it is present in the native enzyme for the entire duration of the simulation (30). However, the simulation also shows that upon mutation of the threonine in alanine the lack of the direct hydrogen bond with the G+2 phosphate group is compensated by a water-mediated hydrogen bond to the backbone of Ala-718 (Figure 8).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The identical religation rate of the wild-type and the mutated enzyme is actually an unexpected result since it has been suggested that Thr-718 plays a role in the right positioning of the 5′ end through a hydrogen bond between the aminoacidic hydroxyl group and the G+2 phosphate group of the scissile strand (8). The MD trajectory confirms the importance of this hydrogen bond since it is present in the native enzyme for the entire duration of the simulation (30). However, the simulation also shows that upon mutation of the threonine in alanine the lack of the direct hydrogen bond with the G+2 phosphate group is compensated by a water-mediated hydrogen bond to the backbone of Ala-718 (Figure 8).…”
Section: Discussionsupporting
confidence: 60%
“…This suggests that the main effect caused by the mutation as detected by experiments carried out at 150 mM KCl ionic strength is a perturbation in the dynamical behavior that alters the control of the DNA strand rotation. In order to sample the dynamical properties of the mutated enzyme, to be correlated with the above reported experimental findings, we have carried out a 3250 ps long MD simulation of the mutated system, and compared it with an identical simulation carried out on the native enzyme (30). …”
Section: Resultsmentioning
confidence: 99%
“…Staker et al posited that this interaction might position the 5Ј-OH end of the cleaved DNA for nucleophilic attack of the 3Ј-phosphotyrosyl bond to effect DNA religation (17); thereby providing an explanation for the lethal phenotype of the T718A mutant (10,12,15). Indeed, recent molecular dynamic simulations of the Topo70-DNA complex further support the formation of a hydrogen bond between Thr 718 and the G ϩ2 phosphate group, consistent with a model whereby enzyme controls the relative position of the ϩ1 base with regard to the active site, by means of hydrogen bonds with the ϩ2 G phosphate group (44). Taken together, these observations indicate that the two mutations A653P and T718A induce opposite effects on enzyme catalysis: A653P enhances (21), whereas T718A decreases DNA religation (14,16).…”
Section: Discussionmentioning
confidence: 59%
“…4B). Biochemical and molecular modeling studies indicate that the linker domain influences cleavage-religation dynamics and equilibrium (14,(29)(30)(31). Structural homology modeling and secondary structure prediction (32,33) suggest that the Top1mt linker domain is less structured and presumably more flexible than the nTop1 linker domain.…”
Section: Discussionmentioning
confidence: 99%